Security and Privacy using Two Fold Encryption Protocol Techniques in Edge Computing (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With deployments of IoT devices and the arrival of 5G fast wireless, placing compute and analytics close to where data is created is making the case for edge computing. Edge computing is transforming the way data is being handled, processed, and delivered from millions of devices around the world. The explosive growth of internet-connected devices – the IoT – along with new applications that require real-time computing power, continues to drive edge-computing systems. Due to several advantages like low latency, Real-Time Availability. Real-time Data Transmission, brings Company and customer together, Edge Computing is used. To overcome several problems regarding security and privacy concerns, this paper provides solution by introducing Secured Two Fold Encryption Protocol in Edge Computing (STFC) based on two encryption schemes namely proxy re-encryption and searchable encryption. This paper particularly focus on securing the data from attackers by providing double encryption scheme. In this paper, Resource Manager is introduced in order to reduce the computational overhead in the encryption process.